1989
DOI: 10.3950/jibiinkoka.92.1359
|View full text |Cite
|
Sign up to set email alerts
|

Ossicular vibration in human temporal bones.

Abstract: Vibration mode of the ossicles was investigated in twelve fresh human temporal bones using a video measuring system (VMS, Technical Insrtument). This system allows one to observe the ossicular vibration and to measure its vibration amplitude (up to 0. 2 micron) and phase angle. In this study the inner and middle ear was kept intact except for two small holes in the tympanic tegmen. These holes were for the observation of ossicular movement and were covered with a thin cover glass during the experiment. The vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
2
7
1
Order By: Relevance
“…The vibration amplitude of the ossicles at the second resonance frequency was smaller than that at the first resonance frequency. At the first resonance frequency, our results were similar to the data of the temporal bones using a video measuring system done by Gyo et al (1987) and Aritomo (1989), except for the stapes vibration mode. This may be caused by the assumptions that the incudo-stapedial joint is fixed, there is no constraint of the stapes footplate movement in the transverse direction, and the effect of the stapedial muscle is not taken into consideration.…”
Section: Ossicular Chainsupporting
confidence: 86%
See 2 more Smart Citations
“…The vibration amplitude of the ossicles at the second resonance frequency was smaller than that at the first resonance frequency. At the first resonance frequency, our results were similar to the data of the temporal bones using a video measuring system done by Gyo et al (1987) and Aritomo (1989), except for the stapes vibration mode. This may be caused by the assumptions that the incudo-stapedial joint is fixed, there is no constraint of the stapes footplate movement in the transverse direction, and the effect of the stapedial muscle is not taken into consideration.…”
Section: Ossicular Chainsupporting
confidence: 86%
“…However, in this paper, these were evaluated from a comparison between the frequency response of the eardrum Although Gyo et al (1987) and Aritomo (1989) suggested the movement of the ossicular axis of rotation, in this paper, for the sake of avoiding the complexity of the analysis, the axis of rotation was assumed to be a fixed straight line from the anterior process of the malleus which was supported by the anterior malleal ligament, to the short process of the incus which was supported by the posterior incudal ligament. Boundary conditions of the displacement continuity were assumed at the incudo-mallear and incudo-stapedial joints.…”
Section: Damping Ratio Of Eardrummentioning
confidence: 99%
See 1 more Smart Citation
“…However, peaks around 800-900 Hz in this model are compatible with those in the measurement. Aritomo [15] reported that the individual difference in displacement of both the umbo and stapes footplate was larger at low frequencies and that some temporal bones showed a clear peak in amplitude at resonance frequency. Therefore, it is considered that the differences mentioned above are within the permissible range.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the standard model has been verified in a previous paper (2) by comparing the measuring results obtained from temporal bones (12) - (14) , and in subjects (15) , with the numerical results obtained from the standard model. In essence, the individual middle ear should be remodeled completely by paying attention to the details of its shape; however, obtaining the clear shapes of the TM and ossicles in individuals has been difficult to date.…”
Section: Validity Of the Analysesmentioning
confidence: 97%